An Investigation on Organizational Charlatan Behaviour and Moral Identity as Predictors of Shame: Importance for Education - Juneman Abraham; Rahma Putri Noka Berline (Journal of Education and Learning (EduLearn), 2015)
Corruption is one of the biggest problems that progressively undermine the life of Indonesian. At the psychosocial level, the Indonesian people, especially the leaders and public officials, many times have been referred to as “the shameless nation”; a designation that is attributed as the cause of the flourishing of corruption. Research breakthrough is needed in the educational world in order to better understand the roots of corruption and the minimal and even the lack of the shame. This predictive correlational study made the organization charlatan behaviour and moral identity as predictors of shame proneness. This study, which was conducted on 208 civil servants and private employees in Jakarta, the capital of Indonesia (111 males, 97 females; mean of age = 32.19 years old, standard deviation of age = 10.495 years), showed that the organizational charlatan behaviour is unable to predict shame, but the moral identity can predict it. Implications of this study’s results for further advanced researches as well as practices in education are elaborated in the Discussion and Suggestions section.